Application of Six Sigma Method for Process Improvement in Reducing Pack Defect of Greenfield Milk (Case Study in PT Greenfield, Malang) - Astuti, Retno; Ikasari, Dhita Morita; Hariri, Rifan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
PT Greenfield has always tried to produce milk in accordance with the standards in order to satisfy the consumer, but the fact showed that there were product defects in PT Greenfields. The defects were occurred in handling after the filling process which caused defects in packaging (pack defect). The aim of this research were knowing the factors that cause the pack defect of Greenfields ESL (Extended Self Life) milk and knowing the priority of proposed improvements which would be used to reduce the number of pack defects of Greenfields ESL milk. Data were analyzed using six sigma methods through define, measure, analyze, and improve phase. The research results showed that the factors caused pack leakage were problems of filling machine, dropping of stacked packs or pack hitting by forklift, carelessness on stuffing, imprecise in placing cartoons on the pallet, human error/carelessness, flabby paper, and high humidity. Filling machine has the greatest value of RPN Risk Priority Number) of FMEA (Failure Mode Effect Analysis). It indicates that the priority of improvements was on filling machine.Keywords: Deffect, FMEA, RPN, six sigma